FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISPEPSIA PADA PASIEN DI WILAYAH KERJA PUSKESMAS BANGKINANG KOTA - Rinda Fithriyana (Universitas Pahlawan, 2018)
People often equate dyspepsia with ulcer disease, because there are similarities between the symptoms of both. Irregular eating patterns and lifestyles that tend to be easily swept away are generally a problem that arises in society. In addition to irregular eating patterns, the types of foods consumed also stimulate the increase in stomach acid such as spicy foods, acids and alcoholic beverages, coffee. The case of dyspepsia in the world reaches 13-14% every year, and cases in Kab.Kampar 2016 by 7%. The purpose of this study was to look at factors related to the incidence of dyspepsia in patients in the work area of Puskesmas Bangkinang Kota in 2017. This study used Cross Sectional design, the sample in this study were 133 outpatients in adult poly. The sampling technique used purposive sampling technique. The measuring tool used is questionnaires with research analysis used are univariate and bivariate. The results of the study found that between diet, the use of AINs drugs and the consumption of food and beverages that stimulate HCL associated with the incidence of dyspepsia in patients in the Work Area Puskesmas Bangkinang City Year 2017 (p value = 0.000, 0.000, 0.000 <0.05). It is expected that the respondent can maintain the diet, and not consume food that can stimulate HCL so that it will worsen the state of dyspepsia by listening to information provided by health workers and counseling during the poly treatment.